Computational design, engineering and manufacturing of a material-efficient 3D printed lattice structure. (December 2020) - Naboni, Roberto; Kunic, Anja; Breseghello, Luca
Building with additive manufacturing is an increasingly relevant research topic in the field of Construction 4.0, where designers are seeking higher levels of automation, complexity and precision compared to conventional construction methods. As an answer to the increasing problem of scarcity of resources, the presented research exploits the potential of Fused Deposition Modelling in the production of a lightweight load-responsive cellular lattice structure at the architectural scale. The article offers an extensive insight into the computational processes involved in the design, engineering, analysis, optimization and fabrication of a material-efficient, fully 3D printed, lattice structure. Material, structure and manufacturing features are integrated within the design development in a comprehensive computational workflow. The article presents methods and results while discussing the project as a material-efficient approach to complex structures.